2007
DOI: 10.1038/sj.bjc.6603593
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 inhibition: effects on tumour growth, cell cycling and lymphangiogenesis in a xenograft model of breast cancer

Abstract: Cyclooxygenase-2 (COX-2) is associated with poor-prognosis breast cancer. We used a nude mouse xenograft model to determine the effects of COX-2 inhibition in breast cancer. Oestrogen receptor (ER)-positive MCF7/HER2-18 and ER-negative MDAMB231 breast cancer cell lines were injected into nude mice and allowed to form tumours. Mice then received either chow containing Celecoxib (a COX-2 inhibitor) or control and tumour growth measured. Tumour proliferation, apoptosis, COX-2, lymphangiogenesis and angiogenesis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 27 publications
7
58
0
1
Order By: Relevance
“…36 Additionally, we show that system is also exquisitely suited to measuring tumor-associated lymphangiogenesis and lymphatic metastasis to local and distant nodes. Although human cancer cell xenografts in immunodeficient mice have been utilized to study tumor-associated lymphangiogenesis and/or lymphatic metastasis, 41,42 to our knowledge, ours is the first syngeneic breast cancer model in immune competent mice showing rapid and spontaneous metastasis of the primary tumor to regional and distant lymph nodes, mimicking aggressive breast cancer in the human. Using this model, this study demonstrated that an EP4 antagonist ONO-AE3-208, but not EP1 antagonist ONO-8713 was highly and equally effective as a COX-2 inhibitor celecoxib in inhibiting primary tumor growth, tumor-associated angiogenesis and lymphangiogenesis, and metastasis to the lymph nodes and the lungs.…”
Section: Therapy With Cox-1/2 Inhibitor Cox-2 Inhibitor or Ep4 Antagmentioning
confidence: 99%
“…36 Additionally, we show that system is also exquisitely suited to measuring tumor-associated lymphangiogenesis and lymphatic metastasis to local and distant nodes. Although human cancer cell xenografts in immunodeficient mice have been utilized to study tumor-associated lymphangiogenesis and/or lymphatic metastasis, 41,42 to our knowledge, ours is the first syngeneic breast cancer model in immune competent mice showing rapid and spontaneous metastasis of the primary tumor to regional and distant lymph nodes, mimicking aggressive breast cancer in the human. Using this model, this study demonstrated that an EP4 antagonist ONO-AE3-208, but not EP1 antagonist ONO-8713 was highly and equally effective as a COX-2 inhibitor celecoxib in inhibiting primary tumor growth, tumor-associated angiogenesis and lymphangiogenesis, and metastasis to the lymph nodes and the lungs.…”
Section: Therapy With Cox-1/2 Inhibitor Cox-2 Inhibitor or Ep4 Antagmentioning
confidence: 99%
“…In other reports, expression of COX-2 protein was also not specifically inhibited by celecoxib. 41,42 Barnes et al 41 reported that COX-2 protein expression was decreased by treatment with celecoxib. However, it seems that the decreased COX-2 expression and antiproliferative effect of celecoxib treatment is more related to apoptosis of tumor cells rather than specific inhibition of COX-2 expression by celecoxib.…”
Section: Notementioning
confidence: 99%
“…However, it seems that the decreased COX-2 expression and antiproliferative effect of celecoxib treatment is more related to apoptosis of tumor cells rather than specific inhibition of COX-2 expression by celecoxib. 41,42 Celecoxib is known to inhibit expression of non-COX-2 targets, such as carbonic anhydrases, 3-phosphoinositide-dependent protein kinase-1, sarcoplasmic/endoplasmic reticulum, and calcium ATPase in tumor cells. Furthermore, celecoxib is known to increase apoptosis of tumor cells via inactivation of Akt, which is a member of the serine/threonine kinase family.…”
Section: Notementioning
confidence: 99%
“…COX-2 is widely expressed in both invasive and preinvasive breast lesions (11) and PGE2 biosynthesis is considered one check point in the mammary carcinogenesis pathway. Moreover, increased PGE2 levels stimulate aromatase transcription (12). Therefore, NSAIDs and selective anti-COX-2 inhibitors may reduce breast cancer risk through the downregulation of aromatase expression (13).…”
Section: Introductionmentioning
confidence: 99%